Children's adjustment in non‐traditional families in Israel: the effect of parental sexual orientation and the number of parents on children's development. Issue 2 (1st November 2011) - Shechner, T.; Slone, M.; Lobel, T. E.; Shechter, R.
Abstract Objectives This study examined differences in children's psychological and social indicators in non‐traditional families in Israel, focusing on fatherless families headed by lesbian mothers and single mothers by choice. Although Israel is considered an industrialized westernized country, centrality of the traditional nuclear family predominates this country. Methods This factorial design study included four family types: lesbian and heterosexual mothers, each in both single and coupled parenthood. Children's measures included the Child Behavior Checklist, perception of peer relations and perceived self‐competence. Results Children from single parent as opposed to two‐parent families exhibited more externalizing behaviour problems and aggressiveness. Children of lesbian mothers reported more prosocial behaviours and less loneliness than children from heterosexual families. No differences emerged for perceived self‐competence across family types. Conclusion Mother's sexual orientation did not affect children's adjustment negatively, whereas single parenthood placed children at greater risk for some difficulties. Implications include the need for apprising health professionals of effects of family types on children's development.